Block structures (restraining bends) and great landslides in the coastal and in Pollino Chains (Northern Calabria - Southern Italy) - Guerricchio, Alessandro (Italian journal of engineering geology and environment, 2018)
<span data-sheets-value=""1":2,"2":"Some block structures present along the faults with weak transcurrent components, crossing the Coastal Chain from SW to NE, due to pushes from south by thrust nappe, especially useful in the seismic field, are identified and described. Some of them are particularly interesting for possible seismic relapse towards the Roggiano Gravina dam, one of the most important hydraulic works in the province of Cosenza. Associated with these structures, there are numerous DSGSDs and large ancient landslides, both in the metamorphic of the Alpine units and in the limestones of the Apennines that distinguish the territory. A hint is also made to the tectonic structure of M.t Pollino Chain, with ancient movements of units with a plastic mechanical behaviour (Liguridi and Sicilidi Units) (Ogniben, 1973) towards N and S in consequence of its raising."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">Some block structures present along the faults with weak transcurrent components, crossing the Coastal Chain from SW to NE, due to pushes from south by thrust nappe, especially useful in the seismic field, are identified and described. Some of them are particularly interesting for possible seismic relapse towards the Roggiano Gravina dam, one of the most important hydraulic works in the province of Cosenza. Associated with these structures, there are numerous DSGSDs and large ancient landslides, both in the metamorphic of the Alpine units and in the limestones of the Apennines that distinguish the territory. A hint is also made to the tectonic structure of M.t Pollino Chain, with ancient movements of units with a plastic mechanical behaviour (Liguridi and Sicilidi Units) (Ogniben, 1973) towards N and S in consequence of its raising.